Co-production of a systematic review on decision coaching: a mixed methods case study within a review - Jull, Janet; Smith, Maureen; Carley, Meg; Stacey, Dawn; Graham, Ian D. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Co-production is a collaborative approach to prepare, plan, conduct, and apply research with those who will use or be impacted by research (knowledge users). Our team of knowledge users and researchers sought to conduct and evaluate co-production of a systematic review on decision coaching. Methods We conducted a mixed-methods case study within a review to describe team co-production of a systematic review. We used the Collaborative Research Framework to support an integrated knowledge translation approach to guide a team through the steps in co-production of a systematic review. The team agreed to conduct self-study as a study within a review to learn from belonging to a co-production research team. A core group that includes a patient partner developed and conducted the study within a review. Data sources were surveys and documents. The study coordinator administered surveys to determine participant preferred and actual levels of engagement, experiences, and perceptions. We included frequency counts, content, and document analysis. Results We describe co-production of a systematic review. Of 17 team members, 14 (82%) agreed to study participation and of those 12 (86%) provided data pre- and post-systematic review. Most participants identified as women (n = 9, 75.0%), researchers (n = 7, 58%), trainees (n = 4, 33%), and/or clinicians (n = 2, 17%) with two patient/caregiver partners (17%). The team self-organized study governance with an executive and Steering Committee and agreed on research co-production actions and strategies. Satisfaction for engagement in the 11 systematic review steps ranged from 75 to 92%, with one participant who did not respond to any of the questions (8%) for all. Participants reported positive experiences with team communication processes (n = 12, 100%), collaboration (n = 12, 100%), and negotiation (n = 10–12, 83–100%). Participants perceived the systematic review as co-produced (n = 12, 100%) with collaborative (n = 8, 67%) and engagement activities to characterize co-production (n = 8, 67%). Participants indicated that they would not change the co-production approach (n = 8, 66%). Five participants (42%) reported team logistics challenges and four (33%) were unaware of challenges. Conclusions Our results indicate that it is feasible to use an integrated knowledge translation approach to conduct a systematic review. We demonstrate the importance of a relational approach to research co-production, and that it is essential to plan and actively support team engagement in the research lifecycle.